Differences between Instagram and Facebook Sponsored Posts for Small Hospitality Businesses (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
In today's age of technological advancement and rapid change, much of the communication takes place on social networks, which offer a great opportunity for customer interaction. Social media is a popular and widely used marketing tool for communication between buyers and sellers. Advertising on social networks is relatively low, which is attractive to businesses, especially smaller ones. This paper aims to study the differences between sponsored content ads on the social networks Facebook and Instagram, using the example of a small hospitality business. The experiment consists of the same text and image posted on the social networks Instagram and Facebook and a post booster run through a mobile app adapted for smartphones. The results show that the promotion of the restaurant business positively affects increasing the number of followers on this page. There are also large differences in response between promoted and non-promoted posts, with promoted posts having a significantly higher response. Differences between Instagram and Facebook are listed, and recommendations for further research are given.